A Small Blemish: Isotretinoin-Induced Microscopic Colitis. Issue 9 (1st September 2022) - Dukate, Loren R.; Pak, Kevin; O'Connell, William; Junga, Zachary
ABSTRACT: Microscopic colitis is a form of colonic inflammation that presents with chronic nonbloody diarrhea that can only be diagnosed histologically with biopsies obtained during colonoscopy. We report a rare case of isotretinoin-induced microscopic colitis in a patient who was prescribed this medication for nodular acne with a 1-year history of nonbloody diarrhea, bloating, cramping, and foul-smelling gas. Cessation of this medication in addition to initiating treatment with budesonide resulted in remission of the patient's symptoms. The presence of chronic diarrhea in patients who are taking isotretinoin should raise suspicion for this condition and warrant further investigation.